Uma história que narro; uma experiência que não conheço : a representação de personagens trans* na literatura brasileira contemporânea - Rocha, Virgínea Novack Santos da (2018)
Based on the contemporary reflections on gender, especially on transsexuality, the purpose of this reflection is to try to establish some relations between these themes and contemporary Brazilian literature. For this, it is performed a critical and a comparative analysis of the narratives. Do fundo do poço se vê a lua, by Joca Reiners Terron (2010); Sérgio Y vai à América, by Alexandre Vidal Porto (2014), and Carlos Henrique Schroeder's As fantasias eletivas (2016), since they all feature a trans * character (respectively Cleo, Sandra and Copi). Thus, it is observed that all narratives presents the same logic of life organization, that is, a cycle of life directly related to the gender identity of the characters. Namely: a family structure that silences and/or excludes the child, a need for geographical displacement and premature death. In this sense, in order to engage in such reflection, we start with Butler's (2016) concept of performativity and Preciado‟s (2014) concept of plasticity of the genre, in order to understand the mechanisms of discursive reiteration of the genre as well as the possibility of counterproduction by half of the break with the limits on the "truth" of bodies. In addition, important contributions are also those of Jesus (2013 and 2014a) and Vergueiro (2016), situating the gender issues in the context of transfeminism, the researchers theorize about the power structure that subjects the trans* identity in our society: the cisnormativity. Thus, it was possible to conclude that in the three narratives there are allusions to the identities of the characters as falsehood, artificiality and copy. Cleo is a trans* woman who tries to build herself up as a usurpation of female stereotypical identities by the cinema; Sandra is a self-conscious woman besides having an excellent financial condition, but ends up having the same fate as the other characters, which, however, is treated under the sign of chance. Finally, Copi is a great representative of the reality of many Brazilian transvestites, since she is relegated to abandonment and solitude. However, their identities are also tied to acting, lies and falsehood.